The colorful community - Islam embraces all colors - Seise, Claudia (Azizah) (aboutislam.net, 2018)
llah created human beings in the most beautiful way and with an amazing diversity. He created men and women from different ethnic groups and tribes. And He wants us to learn from this variety, from different shapes and colors so we can get to know one another (Quran 49: 13).